Good medical practice for regional block’s procedures - Švedienė, Saulė; Ivaškevičius, Juozas (Acta medica Lituanica, 2012)
Scientific and technological advances, changes in the social environment of doctor’s activities have caused a lot of changes in medicine during recent years. The perioperative period is emotionally stressful for patients because of their fears about anesthesia. The anesthesist‘s duty is to guide the patient through this period by managing his fears, establishing the confidence. The patient also has to be aware of the possible risks related to anesthesia. According to the consent process, the patient should be supplied with comprehensive information before the invasive procedures: risks and benefits, all possible alternatives. This enables the patient to make a conscious choice and increases the participation in his own care. Information about postoperative pain treatment would be helpful as the pain relief is influenced by patient’s knowledge and beliefs. In this regard, regional anesthesia can provide a safer alternative to general anesthesia and prolonged postoperative analgesia. Continuous infusion, which is the actual clinical standard, allows to adjust the rate of infusion and concentration of drugs according to patient’s response and to maintain a constant drug level over time. New techniques of the needle tip guidance under ultrasound imaging reduce the fears about the nerve damage as a smaller volume of local anesthetic can be placed at very precise points of the targeted nerve. Continuing professional education is obligatory for good medical practice and professional standards. It includes the development of theoretical knowledge and practical skills in the techniques, communication, teaching, management and clinical responsibilities.